Jóvenes migrantes en el puente transnacional Argentina-España: trayectorias de movilidad social a partir de la movilidad geográfica - Sofía Laíz Moreira (Les Cahiers ALHIM)
This paper presents the main results of a research which objective was to analyze the intergenerational social mobility strategies of Argentine youngsters and their families settled in the Autonomous Community of Galicia, in Spain, at the beginning of this century. An ethnographical methodology using a multisided approach has guided a large field work with ten family groups, which members were settled between Galicia, in Spain, and the Province of Buenos Aires, in Argentina. The measurements in educational and professional categories have taken into account the generation of the parents and that of that of children, that’s to say, from an intergenerational point of view. Results have shown upward educational mobility between generations but poor results in regard to young migrants’ professional insertion.